2012
DOI: 10.2741/3937
|View full text |Cite
|
Sign up to set email alerts
|

A distinctive role for galectin-7 in cancer ?

Abstract: The galectins are a family of evolutionay-conserved carbohydrate-binding proteins. They are distributed widely in all living organisms and have been implicated in many essential functions including development, differentiation, cell-cell adhesion, cell-matrix interaction, growth regulation, apoptosis. Several members of the galectin family have also been shown to be involved in cancer progression and metastasis. In the case of galectin-7, several studies have reported alterations in its expression pattern duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
(88 reference statements)
0
24
0
Order By: Relevance
“…Interestingly, Lee et al [63] claimed that the upregulation of galectin-7 expression occurs in a PGE2-dependent manner as a result of the EC-SOD-mediated activation of COX-2, which leads ultimately to the accumulation of pro-apoptotic molecules, such as caspase-3, caspase-9, Bax, and Bcl-Xs. As to the pathological stress conditions, including cancer, it has been suggested that galectin-7 plays a dual role as a result of its ability to mediate apoptosis and cancer suppression via a p53-dependent pathway and to promote cancer progression via NF-jBdependent pathway [64]. Since both p53 and NF-jB belong to stress-induced transcription factors, the corresponding upregulation of galectin-7 should be considered in the context of specific cellular stress responses with differential outcomes, which fits perfectly with the conceptual paradigm of stress-induced selection between cell death or cell survival.…”
Section: Galectin-7mentioning
confidence: 99%
“…Interestingly, Lee et al [63] claimed that the upregulation of galectin-7 expression occurs in a PGE2-dependent manner as a result of the EC-SOD-mediated activation of COX-2, which leads ultimately to the accumulation of pro-apoptotic molecules, such as caspase-3, caspase-9, Bax, and Bcl-Xs. As to the pathological stress conditions, including cancer, it has been suggested that galectin-7 plays a dual role as a result of its ability to mediate apoptosis and cancer suppression via a p53-dependent pathway and to promote cancer progression via NF-jBdependent pathway [64]. Since both p53 and NF-jB belong to stress-induced transcription factors, the corresponding upregulation of galectin-7 should be considered in the context of specific cellular stress responses with differential outcomes, which fits perfectly with the conceptual paradigm of stress-induced selection between cell death or cell survival.…”
Section: Galectin-7mentioning
confidence: 99%
“…This abnormally high expression level of galectin-7 is not restricted to breast cancer cells. It is also found in pancreatic cancer cell lines [14], and in esophageal, buccal, and hypopharyngeal squamous cell carcinoma [10,1517]. Such high levels of galectin-7 in cancer cells are somewhat paradoxical because galectin-7 has generally been considered a pro-apoptotic protein under the control of p53 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of indications have suggested that galectin-7 may potentially be important in melanoma proliferation, invasion, and metastasis. Like other members of the galectin family, galectin-7 has been shown to either positively or negatively modulate apoptosis and tumor growth [34]. In colon cancer, for example, galectin-7 has an anti-tumorigenic function [15], in contrast to its pro-tumorigenic function reported in lymphoma, breast cancer, squamous cell carcinoma of the tongue and esophagus, and thyroid malignancies [20]-[22], [35][37].…”
Section: Discussionmentioning
confidence: 99%